2021
DOI: 10.3390/ani11051334
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Metabolomic Profiles in Bovine Mammary Epithelial Cells under Essential Amino Acid Restriction

Abstract: Mammary epithelial cells (MECs) in culture are a useful model for elucidating mammary gland metabolism and changes that occur under different nutrient disponibility. MECs were exposed to different treatments: 100% EAA for 8 h and 24 h restriction (R); 2% EAA for 8 h and 24 h R; 2% EAA for 8 h and 24 h + 100% EAA for 8 h and 24 h restriction + re-feeding (R + RF). Western blotting and protein quantification was performed. The Kyoto Encyclopedia of Genes and Genomes (KEGG) software identified the amino acids (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Arginine and proline metabolism and arginine biosynthesis were two common pathways in all four top pathway detected by the both Angus and KC populations, which also supports the results that the Angus and KC populations had more common metabolites that were significantly associated with CH 4 . It was found that the alanine pathway was the center of interactions of many other pathways [49], which implied the activation of this pathway might be related to higher methane emissions. It is reported that Arginine and proline metabolism (detected in Angus and KC population) and Phenylalanine metabolism (detected in KC population) were significantly affected pathway on enteric methane emissions from dairy cows [50].…”
Section: Plos Onementioning
confidence: 99%
“…Arginine and proline metabolism and arginine biosynthesis were two common pathways in all four top pathway detected by the both Angus and KC populations, which also supports the results that the Angus and KC populations had more common metabolites that were significantly associated with CH 4 . It was found that the alanine pathway was the center of interactions of many other pathways [49], which implied the activation of this pathway might be related to higher methane emissions. It is reported that Arginine and proline metabolism (detected in Angus and KC population) and Phenylalanine metabolism (detected in KC population) were significantly affected pathway on enteric methane emissions from dairy cows [50].…”
Section: Plos Onementioning
confidence: 99%